Explaining the Structural Model of the Relationship Between Parental Stress Index and Democratic Parenting Style with the Mediating Role of Wisdom and Sense of Coherence - Moeini, Freshteh; Hosseinpour, Reza; Jafari, Alireza (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to examine the structural model of the relationship between parental stress and democratic parenting style with the mediating role of wisdom and sense of coherence.Methods and Materials: The research method was correlational in terms of design. The statistical population consisted of parents of elementary school students in Tehran during the 2022–2023 academic year, from which 639 individuals were selected through cluster random sampling. Data were collected using the Parental Stress Index (Abidin, 1990), the Ardelt Wisdom Scale (Ardelt, 2003), the Antonovsky Sense of Coherence Scale (Antonovsky, 1993), and the Robinson Authoritative Parenting Questionnaire (Robinson et al., 2001). The data were analyzed using Pearson correlation coefficients and structural equation modeling.Findings: The results showed a negative relationship between parental stress and democratic parenting style (p < .01). The modeling results indicated that the model had a good fit, and wisdom and sense of coherence were able to mediate the relationship between the parental stress index and parenting style.Conclusion: Tthe results demonstrated that the variables of parental stress index, wisdom, and sense of coherence have an impact on democratic parenting style.